Information system audit how to control the digital disruption - Peret, Philippe (Security, audit and leadership series, 2023)
"The digitalization of companies is a recurrent topic of conversation for managers. Companies are forced to evolve at least as fast as their competitors. They have to review their organization, their processes, and their way of working. This also concerns auditors in terms of their audit strategy and working methods. Digitalization is the tip of the iceberg that represents the increasing digitalization of the company's information system. Companies have seen new competitors succeed with a digital approach, competitors that have opened new markets or new ways of interacting with their customers. All business processes can only be digitalized. In this new paradigm, auditors have to renew themselves too. Long gone are the days of auditors specializing in one technique, like financial auditors or IT auditors. This makes it a phenomenal opportunity for auditing to renew itself, embracing the vision of the company's information system: long live the information system auditors! This book proposes how you step by step go from a common understanding of our history of auditing to gradually define and justify the impacts on the audit strategy and the preparation of audits"--